2003
DOI: 10.1080/0003684032000126780
|View full text |Cite
|
Sign up to set email alerts
|

Foreign direct investment in Turkey: regional determinants

Abstract: The uneven regional distribution of foreign direct investment (FDI) in Turkey poses an interesting question from the perspective of multinational firms (MNFs) and policy-makers alike. This paper focuses on the factors governing the location decisions of MNFs within Turkey with specific reference to policy implications. Using a conditional logit model, it is found that agglomeration, depth of local financial markets, human capital, and coastal access dominate location decisions for the aggregate sample of forei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(54 citation statements)
references
References 28 publications
2
50
0
2
Order By: Relevance
“…Therefore, agglomeration of Japanese companies in China was a strong and significant FDI determinant for Japanese SMEs (ibid., p. 16). In the Turkish case, Deichmann, Karidis and Sayek (2003) gave evidence that foreign direct investors prefer the proximity of agglomerations in their location choice decisions. Furthermore, it was found that investors locate in urban areas with coastal access and a highly educated workforce (ibid., 2003, p. 1778).…”
Section: Fdi Location Choice Factors At the Regional Levelmentioning
confidence: 99%
“…Therefore, agglomeration of Japanese companies in China was a strong and significant FDI determinant for Japanese SMEs (ibid., p. 16). In the Turkish case, Deichmann, Karidis and Sayek (2003) gave evidence that foreign direct investors prefer the proximity of agglomerations in their location choice decisions. Furthermore, it was found that investors locate in urban areas with coastal access and a highly educated workforce (ibid., 2003, p. 1778).…”
Section: Fdi Location Choice Factors At the Regional Levelmentioning
confidence: 99%
“…Using a cross-sectional sample of 71 developing countries and the number of telephones per 1,000 inhabitants as a measure of infrastructure development, Asiedu (2002) finds that, while a better infrastructure increases the flow of FDI to non-Sub-Saharan African countries, it has no significant impact on the inflow to Sub-Saharan economies. Using a cross-sectional sample of 293 foreign firms that invested in Turkey in 1995, Deichmann et al (2003) find no evidence that public investment in infrastructure capital attracts foreign multinational firms to locate in Turkey. Other studies of the effect of infrastructure on FDI include those by Wheeler and Mody (1992) and Kumar (1994).…”
Section: The Interaction Between Fdi and Infrastructure Capitalmentioning
confidence: 99%
“…Cheng and Kwan (2000:396), Guimaraes, Figueiredo and Woodward (2000:127) and Gao (2005:290) found positive relationships between senior or secondary education and FDI. Deichmann, Karidis andSayek (2003:1773) found a negative relationship between the student/teacher ratio and FDI in Turkish regions. Gao (2005:289) and Cassidy and Andreosso-O'Callaghan (2006:521) also found a positive relationship between tertiary and college education and FDI in Chinese regions.…”
Section: Empiricsmentioning
confidence: 99%
“…List (2001:971) found a positive link between FDI and the land area of Californian countries and Cheng and Stough (2006:380) found a negative relationship between the cost of land and FDI in Chinese provinces. Deichmann et al (2003Deichmann et al ( :1775 identified a negative link between agricultural value added in a region and FDI in Turkish regions.…”
Section: Empiricsmentioning
confidence: 99%